Strategi Pengembangan Umkm Kuliner Tradisional Melalui Analisis Swot Dan Business Model Canvas(Studi Kasus pada Warung Misop Kampung Yani Mbotz Tanjung Morawa Sumatera Utara) - Sari Sirait, Syah Paradiba (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to analyze the potential and business development strategies of Warung Misop Kampung Yani Mbotz in Tanjung Morawa District as a representative of traditional culinary MSMEs. The main problems identified are limited capital, simple business management, and the lack of digital promotion. This research employs a qualitative descriptive method with a case study approach, using direct observation, interviews with the business owner, and document analysis. Data were analyzed using the SWOT (Strengths, Weaknesses, Opportunities, Threats) framework to identify internal and external factors, and the Business Model Canvas (BMC) to formulate development strategies. The results reveal that the main strengths of the business lie in authentic taste, affordable prices, and customer loyalty. Weaknesses include limited menu innovation, underutilized digital promotion, and the absence of systematic financial recording. Opportunities arise from the growing public interest in traditional culinary products and government support for MSMEs, while threats come from competition with modern food outlets, fast-food chains, and rising raw material prices. The strategies formulated through the BMC framework include product innovation, service diversification, the optimization of social media marketing, and the strengthening of business networks. The study concludes that applying BMC-based strategies can enhance the competitiveness of Warung Misop Kampung Yani Mbotz while preserving traditional culinary heritage. These findings are expected to serve as a reference for other culinary MSMEs in developing their businesses sustainably.